Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran IPAS dengan Menggunakan Model Problem Based Learning (PBL) di Kelas IV SDN 01 Sungai Jariang Kabupaten Agam - Satila, Jihan; Zuardi, Zuardi (TSAQOFAH, 2025)
This study is motivated by the low learning outcomes of students due to the lack of active involvement in the learning process, which is still centered on the teacher. The purpose of this research is to describe the improvement in student learning outcomes in the IPAS lessons on the topic "Landforms and Their Utilization Related to Professions" using the Problem Based Learning (PBL) model in grade IV at SDN 01 Sungai Jariang, Agam Regency. This type of research is Classroom Action Research (CAR) with qualitative and quantitative approaches, conducted in two cycles, each consisting of planning, implementation, observation, and reflection. Data collection techniques used tests and non-tests, with research subjects including the classroom teacher as the practitioner, the researcher as the observer, and 24 students from grade IV. The results of the study indicate an improvement in each observed aspect, where the design of the teaching module increased from 83.3% (B) in cycle I to 95.8% (SB) in cycle II. Teacher and student activities also improved from 78.5% (C) to 96.42% (SB), while the assessment of attitudes showed a decrease in students exhibiting negative behavior. The average learning outcomes from the aspects of knowledge and skills increased from 74.28 (C) to 86.33 (B). Thus, the application of the PBL model has been proven to enhance student learning outcomes in IPAS lessons.